Горящие звезды: стихи и поэмы : перевод с осетинского / Аким Галуев - Галуев Аким Давидович (Советская Россия, 1982)
Экземпляры: ф.14 (20160315) / Инвентарный номер: 011326 / Цена: 0.70 / Авт.знак: Г16 / ГРНТИ: 17.82.10 / ББК: 84(2Рос=Осет)